MINERAL MINERAL CHARACTERISTICS OF BLOCK HERBS WITH THE ADDITION OF TURMERIC FLOUR AND MORINGA LEAF FLOUR - Aurelia Yuliana Dominika Mau; Gomera Bouk (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study was conducted to evaluate the chemical characteristics of herbal mineral Blok supplemented with turmeric flour and moringa leaf flour as a feed supplement for ruminants. The objective of this study was to determine the nutritional characteristics and palatability of herbal mineral Blok with different levels of moringa leaf flour addition. This study used a quantitative descriptive method by analyzing laboratory test results of several treatment samples, namely P0 (1% turmeric flour), P1 (1% turmeric flour + 1% moringa leaf flour), P2 (1% turmeric flour + 2% moringa leaf flour), and P3 (1% turmeric flour + 3% moringa leaf flour). The observed variables included crude protein, crude fat, moisture content, and palatability. The results showed that the addition of moringa leaf flour increased crude protein content from 4.638% in P0 to 5.918% in P3 and increased crude fat content from 5.275% to 6.737%. Moisture content showed relatively stable values among treatments, while palatability evaluation indicated that all treatments were accepted by livestock. The study concluded that the addition of moringa leaf flour up to 3% improved the nutritional characteristics of herbal mineral Blok without reducing feed acceptance.